Parental practices and their association with alcohol and cannabis use among adolescents in Chile - Libuy, Nicolás; Guajardo, Viviana; Ibáñez, Carlos; Araneda, Ana María; Contreras, Lorena; Donoso, Paula; Gaete, Jorge; Mundt, Adrian P. (Frontiers in Psychology, 2023)
Background: Adolescent alcohol and cannabis use are common in Chile. The present research aimed to assess the relationship of perceived parenting practices with alcohol and cannabis use of adolescents in a Latin American context.We adapted and implemented a substance use prevention strategy in Chile, which included surveys of tenth-grade students from six municipalities in the Metropolitan Region of Greater Santiago. We assessed the reliability and factorial structure of the parenting scale with 16 items, which forms part of the survey (see Supplement 1). We dichotomized parenting scores into high (above the median) and low. The association of parenting practices with alcohol and cannabis use in adolescents was assessed using multivariate multilevel regression models.Results: N=7538 tenth-grade students, nested in 118 schools were included in the study. The 16-item scale of parenting practices showed good internal consistency (Omega total = 0.84), and three factors, representing the Relationship between parents and adolescents, Norms and monitoring, and Parents knowing their children's friends and the parents of their children's friends. High total scores of parenting were associated with lower odds of lifetime alcohol use (OR 0.57; 95% CI: 0.49-0.65) and past-month alcohol use (OR 0.63; 95% CI: 0.57-0.70), lifetime drunkenness (OR 0.64; 95% CI: 0.58-0.72) and lifetime cannabis use (OR 0.54; 95% CI: 0.47 -0.61). Above median scores on each parenting subscale were associated with significantly lower odds of substance use. The strongest associations were seen for the subscale Norms and monitoring. Interactions between parenting and gender showed a significantly stronger effect of parenting practices on alcohol and cannabis use in girls.Different types of parenting practices were associated with a lower prevalence of adolescent alcohol and cannabis use. Improving parenting practices has the potential to prevent adolescent substance use in Chile, especially in girls.